Analysis of the Effects of Renewable Energy Mix, Primary Energy Intensity, Population, and GDP per Capita on Greenhouse Gas Emissions in the Energy Sector in ASEAN Countries - Muftiya, Hikmah; Karsinah, Karsinah (Journal of Social Work and Science Education, 2025)
This study aims to examine the effects of population, GDP per capita, primary energy intensity, and the renewable energy mix on greenhouse gas (GHG) emissions in the energy sector across ASEAN countries. A panel data regression analysis was conducted using the Fixed Effects Model (FEM) on annual data from ten ASEAN nations over the period 2000–2020. Robust standard errors clustered by country were applied to address issues of autocorrelation and heteroscedasticity. The results reveal that population growth and higher primary energy intensity are significantly associated with increased GHG emissions, while GDP per capita and the renewable energy mix do not show statistically significant effects. These findings indicate that energy efficiency and demographic trends are key drivers of emissions in the region. The novelty of this study lies in its use of panel econometrics to comprehensively assess multiple variables simultaneously within the context of ASEAN’s energy sector, an area underrepresented in previous research. Practically, the results underscore the need for targeted energy efficiency improvements and integrated population-energy planning in policy formulation. This study contributes empirically to the discourse on sustainable energy transition and provides evidence-based insights for developing climate mitigation strategies tailored to the ASEAN context.